A Validity Study of Malay-translated Version of the Modified Caregivers Strain Index Questionnaire (M-CSI-M) - Ramasamy, Mohan S.; Ibrahim, Rahimah; Madon, Zainal; Arshat, Zarinah (2017)
Objectives The diversity of the population of the world suggests a great need for validated cross cultural survey instruments or scales.Health care professionals should have access to reliable sources and valid concepts of interest in their own cultures and languages to provide quality patient care.Therefore, the aims of this study were to translate the Modified Caregiver Strain Index (M-CSI) in the national language of Malaysia.Also to evaluate the validity and reliability of the Malay-translated version of Modified Caregiver Strain Index (M-CSI-M).Methods Instrument was translated forward and rearward through the translation strategy, reconciled by a panel, and verified by the Malaysian Institute of Translation & books as experts of content.After methodological approaches for the translation, adaptation and transcultural validation of Modified Caregiver Strain Index (M-CSI).The latest version of Malaysia was administered to 50 informal care providers of dependent elderly with the Parkinson’s disease, at the Association of Parkinson Malaysia (MPDA) and University Kebangsaan Malaysia (UKM) Medical Centre in May 2017.Results The Malaysians Modified Caregiver Strain Index (M-CSI-M) has a good face validity and content, as well as inner consistency (Cronbach’s alpha 0.75).In conclusion, the M-CSI-M is a reliable tool for the evaluation of caregiving strain levels experienced by informal care providers in Malaysia.M-CSI-M is recommended as a brief and valid measurement that can be used by doctors, counselors, social workers and psychologists to locate the caregiving strain levels of the informal care providers of dependent elderly in Malaysia.